2021
DOI: 10.3390/ijerph18199960
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Alkali-Activated Lead–Zinc Smelting Slag for Chromite Ore Processing Residue Solidification/Stabilization

Abstract: Lead–zinc smelting slag (LZSS) is regarded as a hazardous waste containing heavy metals that poses a significant threat to the environment. LZSS is rich in aluminosilicate, which has the potential to prepare alkali-activated materials and solidify hazardous waste, realizing hazardous waste cotreatment. In this study, the experiment included two parts; i.e., the preparation of alkali-activated LZSS (pure smelting slag) and chromite ore processing residue (COPR) solidification/stabilization. Single-factor and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The visual appearance of both acid wastes is shown in Figure 1. In this way, recent investigations on the use of geopolymer matrices to solidify/stabilize different hazardous waste-containing heavy metals have been reported: electric arc furnace dust [29][30][31], municipal solid waste incineration fly ash (MSWI) [26], lead-zinc smelting slag [14,[32][33][34], chromite ore processing residues [35,36], hexavalent chromium [37,38], or galvanic solid waste [39], among others. Immobilization efficiency is measured mainly by the mechanical strength and the leaching reduction as indicators of solidification and stabilization, respectively.…”
Section: Acid Wastesmentioning
confidence: 99%
“…The visual appearance of both acid wastes is shown in Figure 1. In this way, recent investigations on the use of geopolymer matrices to solidify/stabilize different hazardous waste-containing heavy metals have been reported: electric arc furnace dust [29][30][31], municipal solid waste incineration fly ash (MSWI) [26], lead-zinc smelting slag [14,[32][33][34], chromite ore processing residues [35,36], hexavalent chromium [37,38], or galvanic solid waste [39], among others. Immobilization efficiency is measured mainly by the mechanical strength and the leaching reduction as indicators of solidification and stabilization, respectively.…”
Section: Acid Wastesmentioning
confidence: 99%
“…23 Many researchers have been focusing on the immobilization of chromium in COPR. 7,9,20 Muhammad et al 2020 (ref. 20) used composite-based geopolymer (BFS and metakaolin) and green tea synthesized nanoscale zerovalent iron (GT-NZVI) to solidify COPR, and they found that the compressive strength of the cured body with GT-NZVI particles was not greatly reduced, but the leaching toxicity was far below the safety limit (5 mg L −1 ), indicating that COPR was effectively solidified in the composite-based geopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies dealing with COPR could be divided into ve main categories: (I) Solidication/stabilization (S/S) technology, [7][8][9] which means that the chromium in COPR is transformed into states and forms that are insoluble, migratory or less toxic by physical and chemical means using some materials such as ordinary Portland cement or alkali-activated cementitious material; (II) chemical reduction technology, including dry-detoxication (utilizing some reducing gases, such as CO) and wet-detoxication (reduction of Cr(VI) to Cr(III) in the liquid phase); [10][11][12] (III) microbial techniques, [13][14][15] i.e. the reduction of Cr(VI) in COPR by microorganisms; (IV) resource utilization methods, 16,17 in which COPR is used as an alternative material to produce certain products, transforming it into useful substances that promote the recycling of waste, such as sintered iron and glass colorants; (V) compound treatment technology, [18][19][20] which refers to using multiple technologies at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that, some metal cations can even participate in the geopolymerization reaction [ 2 , 3 ]. Research to date has shown a lot of results in field of toxic heavy metals treatment by immobilization into alkali activated structure [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%